Komparasi Hasil Belajar Bahasa Arab Siswa dengan Media Gamtem di MI As-Syafi’iyyah Jember - Fina Aunul Kafi; Devi Miftahul Mahasin (INAIFAS PRESS, 2023)
Learning media needs to be adapted to the age of students. To support the success of the learning process, media have been created and modified to make it easier for students to understand the teaching material. This research decided to compare the learning outcomes of students in grades Va and Vb elementery school As-Syafi'iyah Wonorejo Kencong Jember on a‘ḍā' al-jism material using Gamtem media. A qualitative approach helped this research with data collection through observation and documentation. The results of the research showed that Gamtem media applied in class Va was superior in the written test with an average score of 88,95, while class Vb was superior in the oral test with an average score of 78,44. Thus, Gamtem media can support students' success in learning speaking and writing competence.